The development of prosocial behavior from late childhood to adolescence: a longitudinal and multicultural study - Cirimele, Flavia; Pastorelli, Concetta; Remondi, Chiara; Zuffianò, Antonio; Thartori, Eriona; Gerbino, Maria; Di Giunta, Laura; Bacchini, Dario; Oburu, Paul; Skinner, Ann T.; Sorbring, Emma; Steinberg, Laurence; et al. (Frontiers in Developmental Psychology, 2024)
The present study explored the longitudinal trajectory of prosocial behavior in the transition to adolescence (from ages 9 to 16) in a sample of 915 children (Time 1: 50.5% males; Mage = 9.24, SD = 0.69) across six countries (Colombia, Jordan, Italy, the Philippines, Thailand, and the United States) by examining the role of Human Development Index (HDI) in relation to prosocial development. Over four time points covering 7 years, prosocial behavior was assessed using a selfreport measure. A second-order Latent Growth Curve Model, controlling for child gender and family SES, showed that prosocial behavior remained stable in contexts with high HDI, whereas increases in prosocial behavior were evidenced as children moved into adolescence in contexts with low HDI. Moreover, cultural differences in the mean level of prosocial behavior were shown during late childhood and the earliest phase of adolescence, whereas the national development of a given context did not account for differences in prosocial behavior during late adolescence. The role of sociocultural factors in shaping trajectories of prosocial behavior across six countries are discussed. in the majority of the world (i.e., countries that include the majority of the adolescents' population; Khan et al., 2022).Although adolescents across the globe help, comfort, and share with others every day, processes related to the development of prosocial behavior may not be universal (e.g., Pastorelli et al., 2021) and, instead, may vary according to differences in adolescents ' broader lives, communities, and cultures (Bronfenbrenner and Morris, 2007). In this regard, there remains a notable gap in understanding sociocultural factors that influence the expression and development of prosocial behavior in diverse populations (Armstrong-Carter and Telzer, 2021). Exploring the developmental trend of prosocial behavior in a multicultural sample may inform about whether and how